The Search of God in the Mystery According to X. Zubiri - Díaz Muñoz, Guillerma (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2018)
The search of God was a distinctive character of the benedictine oblate life and work of Xavier Zubiri (1898-1983), and the aim of his philosophicaltheological thinking. Here, this pauline category shows its actuality. He adopts the pauline perspective of «enigma» and «mystery», going further in its realistic and dynamic meaning. From this perspective, Zubiri goes deeper into the understanding of the «grope for God» (Hch 17,27). Taking this categories as grounding and cohesive ideas, it is suggested a re-reading of Zubiri’s trilogy on the «human being’s theological problem», and some notions related, as «religación» (religious binding), «religion», «deiformidad» (deiformity), God as problem and Christianity.